Penerapan Pemberian Virgin Coconut Oil (VCO) Pada Asuhan Keperawatan Anak Dengan Gastroenteritis - Desi Ayu Fitriah; Siti Nurhayati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Gastroenteritis is an infectious disease that is one of the causes of death in children. Children with gastroenteritis often experience skin problems in the anal area because they are often exposed to feces. Thin skin is more susceptible to infection, irritation and allergies. The most common skin integrity disorder experienced by children is diaper rash. An intervention that can be carried out by nurses to overcome skin integrity disorders is the administration of Virgin Coconut Oil (VCO). This research aims to reduce diaper rash in children. Descriptive research using a case study and literature approach and the application of Evidence Based Nursing (EBN) to a 17 month old girl with gastroenteritis. Virgin Coconut Oil (VCO) is given to the perineal area for three days and given 4-5 times a day. The instrument used is an area grading scale. The problem of skin integrity disorders in children occurs when the degree of diaper rash decreases from mild to very mild. The expected suggestion is that nurses can utilize the playroom in providing nursing care